Efficient camera path planning algorithm for human motion overview - Yeh, I-Cheng; Lin, Chao-Hung; Chien, Hung-Jen; Lee, Tong-Yee (Computer animation and virtual worlds, 2011)
Camera path planning for character motions is a fundamental and important research topic, benefiting many animation applications. Existing optimal‐based approaches are generally computationally expensive and infeasible for interactive applications. In this paper, we propose an efficient approach that can take many constraints of finding the camera path into account and can potentially enable interactive camera control. Instead of solving a highly complicated camera optimization problem in a spatiotemporal four‐dimensional space, we heuristically determine the camera path based on an efficient greedy‐based tree traversal approach. The experimental results show that the proposed approach can efficiently generate a smooth, informative, and aesthetic camera path that can reveal the significant features of character motions. Moreover, the conducted user study also shows that the generated camera paths are comparable to those of a state‐of‐the‐art approach and those made by professional animators. Copyright © 2011 John Wiley & Sons, Ltd. This paper proposes an efficient approach of finding the camera path for human motion and can potentially enable interactive camera control. Instead of solving a complicated camera optimization problem, we heuristically determine the camera path‐based on an efficient greedy‐based tree traversal approach. The experimental results show that the proposed approach generate a smooth, informative, and aesthetic motion over view efficiently.